Neurofeedback therapy to improve cognitive function in patients with chronic post-stroke attention deficits: a within-subjects comparison - Kleih-Dahms, Sonja C.; Botrel, Loic (Frontiers in Human Neuroscience, 2023)
This study investigated a slow-cortical potential (SCP) neurofeedback therapy approach for rehabilitating chronic attention deficits after stroke. This study is the first attempt to train patients who survived stroke with SCP neurofeedback therapy. We included N=5 participants in a within-subjects follow-up design. We assessed neuropsychological and psychological performance at baseline (four weeks before study onset), before study onset, after neurofeedback training, and at three-months-follow-up. Participants underwent 20 sessions of SCP neurofeedback training. Participants learned to regulate SCPs towards negativity, and we found indications for improved attention after the SCP neurofeedback therapy in some participants. Quality of life improved throughout the study according to engagement in activities of daily living. The self-reported motivation was related to mean SCP activation in two participants. We would like to bring attention to the potential of SCP neurofeedback therapy as a new rehabilitation method for treating post-stroke cognitive deficits. Studies with larger samples are warranted to corroborate the results.